Analysis of pharmacological knowledge and pattern of prescription of medicines of dentists in primary care in the city of Feira de Santana-BA (Research, Society and Development, 2022)
The inappropriate prescription of drugs in dentistry has become a public health problem. The purpose of this study was to analyze the way in which Dental Surgeons (DCs) from Feira de Santana's Primary Care conduct the pharmacological prescription. A total of 26 CDs participated in the survey and answered an online questionnaire through the Google Forms platform. The questionnaire presented socioeconomic questions about the most prescribed drugs and their therapeutic approaches in specific oral situations. Based on the results, it was identified that the drugs chosen by the CDs are Dipyrone (69.30%) as an analgesic, Nimesulide (61.50%) as an anti-inflammatory and Amoxicillin (96.20%) as an antibiotic. In clinical situations, 30.9% of respondents indicate the association of analgesic, anti-inflammatory and antibiotic in cases of dentoalveolar abscess. In cases of pulpitis after endodontic urgency, the majority indicated the use of analgesic and anti-inflammatory (57.7%). In the initial pericoronitis, the associated use of analgesic, anti-inflammatory and 0.12% chlorhexidine (30.9%) was indicated. In situations of simple tooth extraction, a good part reported prescribing anti-inflammatory drugs (53.8%). The prescription of corticosteroids was chosen in post-traumatic situations or invasive surgeries. Antibiotic prophylaxis is usually prescribed by respondents in cases of endocarditis and decompensated diabetes mellitus. Through the findings, it is possible to conclude that dentists are prescribing drugs properly. However, it is essential to develop strategies to always remember the importance of knowledge of drugs and, based on that, promote their conscious prescription.